O potencial ético-formativo do filme Blindness: diálogos sobre educação, literatura e cinema, a partir de Saramago e Adorno - Souza, Adriana Vieira de (2021)
The research has as its main goal the relationship between literature, cinema and education. This is a theoretical-analytical study that had as its object the movie Blindness (2008), by filmmaker Fernando Meirelles, inspired by the literary work Essay on blindness (1995), by José Saramago. The problem relates to the presence of an ethical-formative content capable of circumventing the semi-formative dimension of the industrialized culture and, unlike most mainstream film productions (especially those made in Hollywood studios), enabling the viewer to have a formative experience significant (objective and subjective) averse to the hegemonic cultural industry. As the main hypothesis, although Adorno warns that nothing escapes from the cultural industry system, the idea is that there are products and literary works in this system of business conglomerates that clash with the mainstream model and that Blindness is part of this select group. The main goal was to discuss, through the “ethics” and “training” categories, the notion of cinema as a mediator of educational work with critical potential capable of evading the industrialized culture. It was anchored in the assumptions of the critical theory of society, in the formulations of Theodor Adorno and Max Horkheimer, and in the concepts of emancipation and enlightenment of Immanuel Kant. As a result, it was noticed that Essay on blindness, an inspiring work for Blindness, has critical potential, in particular due to the engagement of José Saramago, who adjusted his political militancy, linked to a progressive perspective, to literary and aesthetic peculiarities, which give to the work an unquestionable value. By exposing a contradiction, an inquietude, a confrontation in its participation in the cultural industry scheme, the movie is capable of disturbing, to the point of making the spectator reflect on his own existence, on the non-identical (the other) that it constitutes as a being, over the time and inhabited and uninhabited spaces, as a mean of facing reality, without, however, being subject to it. Blindness's ethical-formative and, therefore, educational potential characterizes it as an artistic expression, an expression of culture capable of promoting the production of meanings of the unspoken, critical and ethical, which are characterized in a process of cultural training, social and human, and reflections and resignifications of current educational conceptions for the awakening of a critical and emancipatory education.